2004
DOI: 10.1590/s0103-90162004000200005
|View full text |Cite
|
Sign up to set email alerts
|

Rootstocks for 'Tahiti' lime

Abstract: The 'Tahiti' lime (Citrus latifolia Tanaka) is an important commercial citrus cultivar in Brazil. 'Rangpur' lime has being used as its main rootstock, but it is susceptible to root rot caused by Phytophthora, reducing tree longevity. An experiment was set up in a randomized block design, with three trees per plot of each rootstock and four replicates, and run for 12 years, aiming to compare the performance of 'IAC-5 Tahiti' lime, budded on 'Rangpur' lime (Citrus limonia Osb.); 'C-13' citrange (Citrus sinensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
6
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 2 publications
2
8
6
11
Order By: Relevance
“…Our results do not agree with Stenzel & Neves (2004) who reported that juice yield was the highest for 'Rangpur' lime differing from trifoliate orange. However, it should be noted that all the rootstocks induced juice contents above 42%, which according to Gayet et al (1995) is the minimum juice content required for fruits destined to exportation.…”
Section: Juice Percentage (Jp)contrasting
confidence: 99%
See 3 more Smart Citations
“…Our results do not agree with Stenzel & Neves (2004) who reported that juice yield was the highest for 'Rangpur' lime differing from trifoliate orange. However, it should be noted that all the rootstocks induced juice contents above 42%, which according to Gayet et al (1995) is the minimum juice content required for fruits destined to exportation.…”
Section: Juice Percentage (Jp)contrasting
confidence: 99%
“…The obtained results of juice content are very close to those found by IriarteMartel (1993) and by Stenzel & Neves (2004), who reported values between 40.8% to 46.7% and between 36.7 to 47.3% for 'Tahiti' lime, respectively.…”
Section: Juice Percentage (Jp)supporting
confidence: 90%
See 2 more Smart Citations
“…In Maringá, in the state of Paraná, Brazil, different rootstocks did not influence fruit mass and ratio, but did influence juice percentage, soluble solids and acidity of 'IAC-5' PL fruits (Stenzel and Neves, 2004).…”
Section: Fruit Qualitymentioning
confidence: 83%